Research on particle jamming in the openings of a freely laid sieving surface of a vibrating screen - Zaselskyi , V.Y.; Popolov , D.V. (Theory and Practice of Metallurgy, 2024)
The research aimed to study the phenomenon of particle jamming in the openings of a sieving surface freely mounted in the box of a vibrating screen and to develop an analytical dependence for determining the jamming force. The methodology was based on an analytical approach considering the physico-mechanical properties of materials and the kinematic characteristics of the system. Particle jamming was analyzed as a result of dry friction forces and elastic deformation caused by impact loads. The study included theoretical analysis and numerical modeling, which allowed identifying critical system parameters. The results revealed that particle jamming occurs under specific relationships between inertial force, geometric parameters of particles, and sieving surface openings. An analytical dependence was established to predict the jamming force, accounting for material density, deformation parameters, and the kinematic characteristics of the vibrating screen. The scientific novelty lies in developing a jamming model that considers particle elastic deformation and frictional forces, as well as identifying critical parameters affecting this process. The practical significance lies in the potential improvement of vibrating screen designs and optimization of their operating parameters to reduce opening blockages and enhance the efficiency of metallurgical material sieving. The findings can be applied to the development of more efficient sieving surfaces and the reduction of energy costs in metallurgical production.